Battery diaphragm, preparation method thereof and secondary battery

The battery separator with a coating of inorganic and organic particles improves wettability and breakdown voltage resistance, addressing polyolefin separator issues by optimizing coating parameters for enhanced performance and safety in lithium-ion batteries.

CN119153893AActive Publication Date: 2024-12-17SINOMA LITHIUM BATTERY SEPARATOR (NANJING) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411624469.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2024-12-17
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

Polyolefin battery separators in lithium-ion batteries suffer from poor wettability with electrolytes, significant shrinkage at high temperatures, and reduced breakdown voltage resistance due to functional material coatings, which can lead to delamination and decreased performance.

Method used

A battery separator with a coating comprising inorganic particles and organic matter, where the coating surface density, thickness, and permeability are optimized to achieve a peel strength of ≥20gf/15mm and breakdown voltage of ≥0.5kV, using specific mass percentages and densities of inorganic and organic components.

Benefits of technology

The optimized battery separator enhances breakdown voltage resistance and peel strength, improving safety, reducing short-circuit rates, and enhancing charge and discharge efficiency while increasing energy density and cycle life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153893A_ABST
    Figure CN119153893A_ABST
Patent Text Reader

Abstract

The invention provides a battery diaphragm, a preparation method thereof and a secondary battery. The battery diaphragm comprises a porous base material layer and a coating, the coating comprises inorganic particles and an organic matter, the coating surface density of the coating is C g / m < 2 >, the coating thickness is H [mu] m, the air permeability increase value of the battery diaphragm is P s / 100 cc, the true density of the inorganic particles is D1 g / cm < 3 >, the density of the organic matter is D2i g / cm < 3 >, the mass percentage content of the inorganic particles in the coating is W1, the mass percentage content of the organic matter in the coating is W2i, and (1-C / H / A) * P / H is larger than or equal to 2 and smaller than or equal to 10. A is the sum of D1 * W1 and the product of the density D2i and the mass percentage W2i of the n organic matters in the coating; the peel strength between the coating and the porous base material layer is greater than or equal to 20 gf / 15 mm, and the breakdown voltage of the battery diaphragm is greater than or equal to 0.5 kV.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical technology, and in particular to a battery separator, a preparation method thereof, and a secondary battery. Background Art

[0002] With the continuous development of society, energy and environmental issues have become increasingly hot topics. Secondary batteries, such as lithium-ion batteries, as a new type of energy storage device, have the advantages of high charge and discharge voltage platform, long cycle life, no pollution, and low self-discharge. Lithium-ion batteries are mainly composed of four parts: positive electrode, negative electrode, electrolyte, and separator. Among them, the battery separator is one of the key components of lithium-ion batteries. Its main functions are twofold: (1) to prevent the positive and negative electrodes from directly contacting and short-circuiting; (2) to absorb electrolyte and provide a channel for the migration of lithium ions.

[0003] Over the past few decades, polyolefin battery separators have been widely used in lithium-ion batteries due to their excellent chemical stability, good mechanical strength, and low price. However, polyolefin battery separators still have many defects, such as poor wettability with electrolytes and significant shrinkage at high temperatures. To address these issues, existing technologies typically coat one or more layers of functional materials on the porous substrate layer of polyolefin battery separators. However, the introduction of functional materials also deteriorates the insulation and stability of the coated battery separator, resulting in a decrease in the battery separator's ability to withstand breakdown voltage. In addition, if the adhesion between the functional material coating and the porous substrate layer is low, there is a risk of delamination between the coating and the porous substrate layer, affecting the performance of the battery separator. Summary of the Invention

[0004] The purpose of this application is to provide a battery separator with strong breakdown voltage resistance and high peel strength, a preparation method thereof, and a secondary battery. The specific technical solution is as follows: The first aspect of the present application provides a battery separator, comprising a porous substrate layer and a coating disposed on at least one surface of the porous substrate layer, wherein the coating comprises inorganic particles and organic matter, and the coating surface density of the coating is C g / m 2 , the coating thickness is H μm, the permeability increase of the battery separator is P s / 100cc, and the true density of the inorganic particles is D1 g / cm 3 , the density of organic matter is D 2i g / cm 3 Based on the mass of the coating, the mass percentage of inorganic particles is W1, and the mass percentage of organic matter is W 2i , satisfying: 2≤(1-C / H / A)×P / H≤10, where, , n is the number of types of organic matter; the peel strength between the coating and the porous substrate layer is ≥20gf / 15mm, and the breakdown voltage of the battery separator is ≥0.5kV.

[0005] In some embodiments of the present application, the mass percentage of inorganic particles satisfies: 82%≤W1≤97%, and the mass percentage of organic matter satisfies: 3%≤ ≤18%.

[0006] In some embodiments of the present application, the thickness of the coating satisfies: 0.5≤H≤8, and the coating area density of the coating satisfies: 1≤C≤10.

[0007] In some embodiments of the present application, the bulk density of the inorganic particles is D3 g / cm 3 , inorganic particles satisfy: 2.3≤D1-D3≤3.1.

[0008] In some embodiments of the present application, the particle size PSD (Particle Size Distribution) of the inorganic particles satisfies: 0.38 μm ≤ PSD ≤ 0.63 μm, wherein, .

[0009] In some embodiments of the present application, the surface hydroxyl groups of the inorganic particles account for 0 to 0.06% by mass.

[0010] In some embodiments of the present application, the inorganic particles are selected from at least one of silica, alumina, magnesia, zirconia, titanium oxide, calcium oxide, boehmite, aluminum nitride, boron nitride, barium sulfate, calcium fluoride, barium fluoride, or barium titanate.

[0011] In some embodiments of the present application, the organic matter includes a first organic matter, and the first organic matter is selected from at least one of styrene-butadiene rubber, acrylic resin, polyvinyl alcohol, polyacrylonitrile, polyvinylidene fluoride, polyethylene oxide, polytetrafluoroethylene, acrylic acid and its derivative copolymers or acrylamide and its derivative copolymers. Optionally, the first organic matter can be one of polyvinylidene fluoride or acrylic resin or a combination thereof. Based on the mass of the coating, the mass percentage of the first organic matter is W 21 , meeting: 3%≤W 21 ≤10%.

[0012] In some embodiments of the present application, the glass transition temperature (T g ) is -40°C to 100°C, and the temperature range of the glass transition temperature is ≤12°C, wherein the temperature range of the glass transition temperature is the difference between the end point and the starting point of the glass transition temperature.

[0013] In some embodiments of the present application, the swelling ratio of the first organic matter in the electrolyte is 40% to 150%.

[0014] In some embodiments of the present application, the shear retention rate of the first organic matter is 0 to 0.08%.

[0015] In some embodiments of the present application, the peel strength between the coating layer and the porous substrate layer is ≥39 gf / 15 mm, and the breakdown voltage of the battery separator is ≥1.70 kV.

[0016] The second aspect of the present application provides a method for preparing the battery separator provided in the first aspect of the present application, comprising the following steps: (1) providing a porous substrate layer; (2) providing a coating slurry comprising inorganic particles and organic matter, wherein the organic matter comprises a first organic matter; (3) coating the coating slurry on at least one surface of the porous substrate layer, and drying the coating slurry to obtain a battery separator comprising a coating.

[0017] In some embodiments of the present application, the coating slurry includes 30-50 parts of inorganic particles, 2-10 parts of the first organic matter, and 40-70 parts of a solvent.

[0018] In some embodiments of the present application, when the first organic matter is added to the coating slurry, the flow rate of the first organic matter is 3 L / min to 9 L / min, and the temperature of the coating slurry is 18° C. to 30° C.

[0019] In some embodiments of the present application, the pH of the coating slurry is 7 to 10, the viscosity is 5 to 200 mPa·s, and the PSD of the particles in the coating slurry is 0.25 μm to 0.5 μm.

[0020] In some embodiments of the present application, during the coating process of the coating slurry, the ratio of the adsorption roller frequency to the thickness of the porous substrate layer is 4.8 Hz / μm to 6 Hz / μm.

[0021] In some embodiments of the present application, the absolute difference between the oven temperature of the drying process and the glass transition temperature of the first organic matter is 20° C. to 65° C.

[0022] The third aspect of the present application provides a secondary battery, which includes the battery separator provided in the first aspect of the present application or the battery separator prepared by the preparation method provided in the second aspect.

[0023] Beneficial effects of this application: This application provides a battery separator, a preparation method thereof, and a secondary battery. The peel strength between the coating and the porous substrate layer is ≥20gf / 15mm, and the breakdown voltage of the battery separator is ≥0.5kV. The battery separator of the application has good breakdown voltage resistance and high peel strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other embodiments can also be obtained based on these drawings.

[0025] Figure 1 This is a schematic structural diagram of a battery separator according to one embodiment of the present application along its thickness direction.

[0026] Reference numerals: battery separator 10 , porous substrate layer 11 , coating layer 12 . DETAILED DESCRIPTION

[0027] The following will be combined with the accompanying drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the embodiments described are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on this application are within the scope of protection of this application.

[0028] The first aspect of the present application provides a battery separator, comprising a porous substrate layer and a coating disposed on at least one surface of the porous substrate layer, wherein the coating comprises inorganic particles and organic matter, and the coating surface density of the coating is C g / m 2 , the coating thickness is H μm, the permeability increase of the battery separator is P s / 100cc, and the true density of the inorganic particles is D1 g / cm 3 , the density of organic matter is D 2i g / cm 3 Based on the mass of the coating, the mass percentage of inorganic particles is W1, and the mass percentage of organic matter is W 2i , satisfying: 2≤(1-C / H / A)×P / H≤10, where, , n is the number of types of organic matter. For example, the value of (1-C / H / A)×P / H can be 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10 or a range consisting of any two values ​​therein. The peel strength between the coating and the porous substrate layer is ≥20gf / 15mm, and the breakdown voltage of the battery separator is ≥0.5kV. In this application, the permeability increase of the battery separator is the difference between the permeability of the battery separator and the permeability of the porous substrate layer. The true density refers to the actual volume of solid matter within the volume of the material in an absolutely dense state, excluding internal pores or voids between particles. When the coating includes two or more organic substances, D in A 2i ×W 2iIt is the product of the density of each organic matter and its mass percentage.

[0029] The inventors of this application have found that in the preparation of battery separators, the properties of the materials determine the affinity between the battery separator and the electrolyte, the liquid absorption and retention rate, and the ion transmission efficiency. By selecting the true density of the inorganic particles and the density of the organic matter in the coating, inorganic particles and organic matter that are beneficial to improving the affinity between the battery separator and the electrolyte, the liquid absorption and retention rate, and the ion transmission efficiency are screened out and applied to the battery separator. The improvement of the above properties of the battery separator can improve its ability to resist breakdown voltage and peel strength; at the same time, by regulating the mass percentage of the inorganic particles and organic matter in the coating, the battery separator can be further improved. The amount, the increase in the permeability of the battery separator, the coating surface density and the coating thickness can improve the porosity, pore size and pore size distribution of the battery separator to further improve the battery separator's breakdown voltage capability and peel strength. Furthermore, by regulating the above parameters of the battery separator to meet 2≤(1-C / H / A)×P / H≤10, the battery separator's breakdown voltage capability and peel strength can be further improved, so that the peel strength between the coating and the porous substrate layer is ≥20gf / 15mm and the breakdown voltage of the battery separator is ≥0.5kV. The application of the above battery separator in secondary batteries can reduce the short-circuit rate of the secondary battery, improve safety, reduce the internal resistance of the battery to improve its charge and discharge efficiency, increase energy density and improve cycle life.

[0030] When the value of (1-C / H / A)×P / H is too small, for example, less than 2, the gaps between the inorganic particles and the organic matter are too large. Although this can improve the lithium ion transmission rate to a certain extent, the gaps formed also significantly increase the electron transmission rate, resulting in a decrease in the resistance of the battery separator, a decrease in the breakdown voltage, and a decrease in the breakdown voltage resistance, affecting the safety performance of the secondary battery. When the value of (1-C / H / A)×P / H is too large, for example, greater than 10, the inorganic particles in the coating are unevenly distributed, resulting in excessive resistance to lithium ion migration, which reduces the lithium ion transmission rate. In addition, the organic matter will partially penetrate into the micropores of the porous substrate layer, forming electron channels in the micropores of the porous substrate layer. This reduces the breakdown voltage of the battery separator and the breakdown voltage resistance, resulting in an increase in the internal resistance of the secondary battery and poor cycle performance.

[0031] In some embodiments, the peel strength between the coating layer and the porous substrate layer is from 20 gf / 15 mm to 500 gf / 15 mm. For example, the peel strength between the coating layer and the porous substrate layer can be 20 gf / 15 mm, 24 gf / 15 mm, 28 gf / 15 mm, 30 gf / 15 mm, 35 gf / 15 mm, 39 gf / 15 mm, 40 gf / 15 mm, 42 gf / 15 mm, 45 gf / 15 mm, 48 gf / 15 mm, 50 gf / 15 mm, 52 gf / 15 mm, 55 gf / 15 mm, 15mm, 60gf / 15mm, 80gf / 15mm, 100gf / 15mm, 130gf / 15mm, 170gf / 15mm, 200gf / 15mm, 250gf / 15mm, 300gf / 15mm, 350gf / 15mm, 400gf / 15mm, 450gf / 15mm, 500gf / 15mm or a range consisting of any two of these values.

[0032] In some embodiments, the breakdown voltage of the battery separator is 0.5 kV to 8 kV. For example, the breakdown voltage of the battery separator can be 0.5 kV, 0.7 kV, 0.9 kV, 1 kV, 1.2 kV, 1.32 kV, 1.35 kV, 1.4 kV, 1.5 kV, 1.6 kV, 1.65 kV, 1.7 kV, 1.75 kV, 1.79 kV, 1.8 kV, 1.83 kV, 1.85 kV, 1.88 kV, 1.89 kV, 1.9 kV, 1.91 kV, 1.95 kV, 2 kV, 2.5 kV, 3 kV, 3.5 kV, 4 kV, 4.5 kV, 5 kV, 6 kV, 7 kV, 8 kV, or a range consisting of any two values ​​therein.

[0033] For ease of understanding, in this application, the length direction of the battery separator itself is defined as X, and the thickness direction is defined as Y. The battery separator generally has a long side and a short side, and the length direction is the extension direction of the long side of the battery separator. It should be understood that the above definition of direction is for the purpose of convenient description of this application. Figure 1 As shown, the battery separator 10 includes a porous substrate layer 11 and coating layers 12 respectively disposed on two surfaces of the porous substrate layer 11 .

[0034] In some embodiments of the present application, the mass percentage of the inorganic particles satisfies the following: 82% ≤ W1 ≤ 97%. For example, the value of W1 can be 82%, 85%, 87%, 90%, 92%, 92.5%, 94%, 94.4%, 95%, 95.2%, 97%, or a range consisting of any two of these values. By regulating the value of W1 within the above range, it is beneficial to improve the heat resistance of the battery separator, while at the same time providing a high peel strength between the coating and the porous substrate layer, which is beneficial to improving the breakdown voltage resistance and peel strength of the battery separator.

[0035] In some embodiments of the present application, the mass percentage of organic matter satisfies: 3%≤ ≤18%. For example, The value of can be 3%, 4%, 4.9%, 5%, 5.7%, 6%, 7%, 7.5%, 9%, 11%, 13%, 15%, 18%, or a range consisting of any two of these values. By adjusting the mass percentage of the organic matter to meet the above conditions, the inorganic particles can be well dispersed in the coating slurry, which is conducive to preparing a coating with uniform distribution of the various components, making the battery separator have good heat resistance, and improving the battery separator's anti-breakdown voltage capability and peel strength.

[0036] In some embodiments of the present application, the thickness of the coating satisfies: 0.5≤H≤8. For example, the value of H can be 0.5, 1, 1.9, 2, 2.1, 2.2, 3, 5, 5.2, 6, 7, 7.1, 8, or a range consisting of any two of these values. By regulating the value of the thickness H of the coating within the above range, it is beneficial to improve the wettability of the electrolyte to the battery separator, improve the peel strength between the coating and the porous substrate layer, and the heat resistance of the battery separator, which is beneficial to improving the breakdown voltage capability and peel strength of the battery separator. Application in secondary batteries is also beneficial to improving their safety performance and energy density.

[0037] In this application, when a coating is provided on only one side of the battery separator, the thickness of the coating refers to the thickness of the coating on that single side; when a coating is provided on both sides of the battery separator, the thickness of the coating refers to the sum of the thicknesses of the coatings on both sides.

[0038] In some embodiments of the present application, the coating surface density of the coating satisfies: 1≤C≤10. For example, the value of C can be 1, 1.5, 2, 2.5, 2.8, 2.91, 2.96, 3, 3.11, 3.21, 3.5, 4, 4.5, 5, 6, 7, 8, 9, 10 or a range consisting of any two of these values. By regulating the value of the coating surface density C of the coating within the above range, it is beneficial to improve the wettability of the electrolyte to the battery separator, improve the peel strength between the coating and the porous substrate layer and the heat resistance of the battery separator, and help improve the anti-breakdown voltage capability and peel strength of the battery separator. Application in secondary batteries is also beneficial to improve its safety performance and energy density.

[0039] In this application, when the battery separator is coated on only one side, the coating surface density of the coating refers to the single-sided coating surface density of the coating; when the battery separator is coated on both sides, the coating surface density of the coating refers to the sum of the coating surface densities on both sides of the coating.

[0040] In some embodiments, the battery separator's air permeability gain satisfies the following condition: 10 ≤ P ≤ 30. For example, P can be 10, 11, 12, 13, 15, 17, 18, 20, 22, 25, 28, 30, or a range consisting of any two of these values. By regulating the air permeability gain P of the battery separator within this range, it is advantageous to improve the battery separator's breakdown voltage capability and peel strength while also enhancing ion transmission efficiency.

[0041] In some embodiments, the true density of the inorganic particles satisfies: 2≤D1≤5. For example, the value of D1 can be 2, 2.5, 3, 3.04, 3.5, 3.91, 4, 4.5, 5, or a range consisting of any two of these values.

[0042] In some embodiments, the density of the organic matter satisfies: 0.9≤D 2i ≤3. For example, D 2i The value of can be 0.9, 1, 1.02, 1.15, 1.2, 1.5, 1.8, 2.0, 2.3, 2.5, 2.8, 3 or a range consisting of any two values ​​therein.

[0043] In some embodiments of the present application, the bulk density of the inorganic particles is D3 g / cm 3, the inorganic particles satisfy: 2.3≤D1-D3≤3.1. For example, the value of D1-D3 can be 2.3, 2.4, 2.5, 2.6, 2.62, 2.7, 2.8, 2.9, 2.98, 3.0, 3.1 or a range consisting of any two of these values. By regulating the value of D1-D3 of the inorganic particles within the above range, the cohesion between the inorganic particles can be improved, and the organic matter in the coating can be better compatible, which is beneficial to the dispersion of the inorganic particles in the solvent, improving the stability and uniformity of the coating slurry, and extending the storage time of the coating slurry. At the same time, it can also maintain a good morphology during the coating slurry transportation and high-speed coating process, improve the density of the coating after coating and the distribution of the organic material in the thickness direction of the coating, reduce the distribution of the organic material between the inorganic particles, make the organic material more distributed at the contact position between the coating and the porous substrate layer, improve the peel strength between the coating and the porous substrate layer, thereby helping to improve the anti-breakdown voltage capability and peel strength of the battery separator. In this application, loose packed density refers to the bulk density measured after the powder freely fills a standard container under specified conditions, that is, the mass per unit volume of the powder when loosely packed.

[0044] In some embodiments, the inorganic particles have a bulk density that satisfies: 0.2≤D3≤1.2. For example, the value of D3 can be 0.2, 0.3, 0.4, 0.42, 0.5, 0.6, 0.7, 0.8, 0.9, 0.93, 1.0, 1.1, 1.2, or a range consisting of any two of these values.

[0045] In some embodiments of the present application, the particle size PSD of the inorganic particles satisfies: 0.38 μm ≤ PSD ≤ 0.63 μm. For example, the value of PSD may be 0.38 μm, 0.40 μm, 0.50 μm, 0.51 μm, 0.60 μm, 0.61 μm, 0.62 μm, 0.63 μm, or a range consisting of any two values ​​thereof, wherein, .

[0046] By regulating the PSD of the inorganic particles within the above range, the inorganic particles are evenly distributed, making the coating surface of the battery separator smooth, which is beneficial to improving the breakdown voltage resistance and peel strength of the battery separator.

[0047] In some embodiments of the present application, the surface hydroxyl mass ratio of the inorganic particles is 0 to 0.06%, preferably 0 to 0.04%. For example, the surface hydroxyl mass ratio of the inorganic particles can be 0%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06% or a range consisting of any two of these values. By regulating the surface hydroxyl mass ratio of the inorganic particles within the above range, it is beneficial to disperse the inorganic particles in the solvent. At the same time, after the organic matter is added, the reaction with it can be reduced, which is more conducive to the coating of the inorganic particles by the organic matter, improves the stability of the coating slurry, and makes the distribution of the components of the prepared coating more uniform, which is beneficial to improving the anti-breakdown voltage capability and peel strength of the battery separator.

[0048] In this application, the surface hydroxyl mass ratio of the inorganic particles can be obtained by the following test method: (1) Preparation of NaCl solution: Weigh 400 g of NaCl into a 2 L beaker, add 1.75 L of water to dissolve, adjust the pH to 3.0 ± 0.1 with hydrochloric acid, and take 150 ml of the above NaCl solution; (2) Preparation of sodium hydroxide standard solution: c(NaOH) = 0.1 mol / L, according to GB / T 601-2016 Chapter 4 4.1 Preparation and calibration of sodium hydroxide standard titration solution; (3) Blank sample addition: titrate with NaOH standard solution at a rate of 20 seconds / drop. When the pH value of the solution reaches 4.0±0.1, the scale value at this time is recorded as V1; continue titrating until the pH reaches 9.0±0.1. After the pH value of the solution reaches 8.0, reduce the titration speed to 20 seconds / half drop. When the pH value changes less than 0.02 within 10 seconds, record the burette scale V2 and calculate the volume of sodium hydroxide solution consumed during the period from pH 4.0 to 9.0 (V) 空白 =V2-V1; (4) Preparation of sample solution: Weigh the inorganic particle sample m after drying at 105℃ for 2h using an analytical balance. 样品 Place 1.5 g (accurate to 1 mg) in a 250 ml beaker, add 150 ml of sodium chloride solution, place a stirring bar in a magnetic stirrer and stir evenly, then keep the temperature at 25 ± 0.5 ° C and titrate; (5) Sample titration: titrate the inorganic particle sample solution at a rate of 3-4 drops per second. When the pH value reaches the end point, slow down the titration speed and record and calculate the volume of sodium hydroxide standard solution V consumed when the solution pH changes from 4.0 to 9.0. NaOH ; (6) Calculation of surface hydroxyl mass ratio: w(OH)=(V NaOH -V 空白 )×c(NaOH)×17.007 / (m 样品×1000), where V NaOH 、V 空白 The unit of is mL, the unit of c(NaOH) is mol / L, m 样品 The unit is g.

[0049] In some embodiments of the present application, the inorganic particles are selected from oxide particles such as silicon dioxide (SiO2), aluminum oxide (Al2O3), magnesium oxide (MgO), zirconium oxide (ZrO2), titanium oxide (TiO2), and calcium oxide (CaO); nitride particles such as boehmite (ALOOH), aluminum nitride (AlN), and boron nitride (BN); crystalline particles of sparingly soluble ions such as barium sulfate (BaSO4), calcium fluoride (CaF2), and barium fluoride (BaF2); and barium titanate (BaTiO3) particles with a high dielectric constant and low dielectric loss. These inorganic particles have stable electrochemical properties and lithium ion transfer capabilities, conducting lithium ions in the electrolyte and promoting lithium ion transport. The use of these inorganic particles also improves the heat resistance of the battery separator and enhances its breakdown voltage and peel strength. Among these inorganic particles, oxide particles are preferred due to their stability and potential in the electrolyte. In addition, the inorganic particles must have a high thermal decomposition temperature (decomposition temperature greater than 500°C) and low water absorption. Alumina, boehmite, magnesium oxide, and silica are preferred, with alumina, boehmite, and silica being more preferred. When two or more inorganic particles are used, the ratio of the inorganic particles is not particularly limited, as long as the objectives of this application can be achieved.

[0050] In some embodiments, in addition to the aforementioned inorganic particles, the coating may further include at least one of lithium phosphate, lithium titanium phosphate, lithium aluminum titanium phosphate, lithium nitride, lithium carbonate, lithium chloride, lithium sulfide, or lithium hexafluorophosphate. These materials have lithium ion transfer capabilities and can enhance the coating's ability to conduct lithium ions.

[0051] The present application does not particularly limit the shape of the inorganic particles, as long as the purpose of the present application can be achieved. For example, the inorganic particles can be in the shape of plates, flakes, needles, columns, spheres, polyhedrons, blocks, etc., and a combination of inorganic particles having multiple shapes can also be used. Preferably, the inorganic particles are in the shape of plates, blocks, polyhedrons, or columns with multiple faces, thereby improving the permeability of ions in the electrolyte through the battery separator.

[0052] In some embodiments, the dielectric constant of the inorganic particles is ≥ 5. When the dielectric constant of the inorganic particles is within the above range, the inorganic particles have stable electrochemical properties and good lithium ion transfer ability, which is beneficial to improving the breakdown voltage resistance and peel strength of the battery separator.

[0053] In some embodiments, the D of the inorganic particles V 50 is 0.01μm to 2μm, and the specific surface area is 0 to 30m 2 / g, preferably 2m 2 / g to 20m 2 / g, more preferably 3m 2 / g to 18m 2 / g. For example, the D V 50 can be 0.01 μm, 0.2 μm, 0.5 μm, 0.7 μm, 1 μm, 1.3 μm, 1.5 μm, 1.8 μm, 2 μm or a range consisting of any two of these values. The specific surface area of ​​the inorganic particles can be 0 m 2 / g, 2m 2 / g、3m 2 / g、5m 2 / g、10m 2 / g、15m 2 / g、18m 2 / g, 20m 2 / g、22m 2 / g, 25m 2 / g、30m 2 / g or a range consisting of any two values. By regulating the D V 50 and the specific surface area are within the above ranges, which can increase the surface energy of the inorganic particles, improve the wettability of the electrolyte to the battery separator, and also improve the fluidity of the coating slurry and the cohesion between the inorganic particles, thereby improving the uniformity and stability of the coating slurry, and reducing the risk of uneven coating of the coating slurry due to high-speed shearing during the coating process, which is beneficial to the preparation of a coating with uniform distribution of components and improving the permeability of lithium ions in the electrolyte in the battery separator; at the same time, it can also reduce the water content in the battery separator and reduce the side reactions caused by the presence of water, thereby helping to improve the anti-breakdown voltage capability and peel strength of the battery separator and improve the performance of the secondary battery, such as the cycle performance.

[0054] In this application, Dv10 refers to the particle size at which 10% of the volume is accumulated, measured from the small particle size, in the volume-based particle size distribution of the material; Dv25 refers to the particle size at which 25% of the volume is accumulated, measured from the small particle size, in the volume-based particle size distribution of the material; Dv50 refers to the particle size at which 50% of the volume is accumulated, measured from the small particle size, in the volume-based particle size distribution of the material; Dv75 refers to the particle size at which 75% of the volume is accumulated, measured from the small particle size, in the volume-based particle size distribution of the material; and Dv90 refers to the particle size at which 90% of the volume is accumulated, measured from the small particle size, in the volume-based particle size distribution of the material.

[0055] Typically, inorganic particles with different PSDs, Dv50s, and specific surface areas can be obtained through mechanical crushing (e.g., ball milling). For example, the PSD, Dv50, and specific surface area of ​​inorganic particles can be manipulated by controlling the ball milling time. When other conditions remain unchanged, a longer ball milling time decreases the PSD of the inorganic particles; a shorter ball milling time increases the PSD of the inorganic particles. When other conditions remain unchanged, a longer ball milling time decreases the Dv50 of the inorganic particles; a shorter ball milling time increases the Dv50 of the inorganic particles. When other conditions remain unchanged, a longer ball milling time increases the specific surface area of ​​the inorganic particles; a shorter ball milling time decreases the specific surface area of ​​the inorganic particles. Furthermore, the particle size distribution of the inorganic particles can be controlled by varying process parameters such as the material-to-ball ratio in the ball mill.

[0056] In some embodiments of the present application, the organic material includes a first organic material selected from at least one of styrene-butadiene rubber, acrylic resin, polyvinyl alcohol, polyacrylonitrile, polyvinylidene fluoride, polyethylene oxide, polytetrafluoroethylene, copolymers of acrylic acid and its derivatives, or copolymers of acrylamide and its derivatives. Alternatively, the first organic material may be polyvinylidene fluoride or acrylic resin, or a combination thereof. The first organic material serves as a binder. The use of the first organic material maintains the mechanical strength and flexibility of the porous substrate layer, imparting excellent mechanical properties to the battery separator. This reduces the risk of inorganic particles falling off the porous substrate layer during secondary battery preparation (e.g., winding), and enhances the peel strength between the coating and the porous substrate layer, thereby improving the breakdown voltage resistance and peel strength of the battery separator.

[0057] The first organic compound of the present application has stable electrochemical performance, which is mainly manifested in that within a voltage range of 1V to 5V, except for the electrode lithium desorption / insertion redox peak, there are no other redox current peaks.

[0058] In some embodiments of the present application, the mass percentage of organic matter is W based on the mass of the coating. 2i , meeting: 3%≤W 2i ≤18%. For example, W 2i The value of can be 3%, 4%, 4.1%, 4.9%, 5%, 6%, 6.5%, 7%, 8%, 9%, 10%, 12%, 14%, 15%, 16%, 18% or a range consisting of any two of these values.

[0059] In some embodiments of the present application, based on the mass of the coating, the mass percentage of the first organic matter is W 21 , meeting: 3%≤W 21 ≤10%. For example, W 21The value of can be 3%, 4%, 4.1%, 4.9%, 5%, 6%, 6.5%, 7%, 8%, 9%, 10% or a range consisting of any two of them. 21 The value of is within the above range, which can ensure good adhesion between the inorganic particles, reduce the shedding of inorganic particles, improve the peeling strength between the coating and the porous substrate layer and the heat resistance of the battery separator, thereby helping to improve the battery separator's anti-breakdown voltage capability and peeling strength.

[0060] In some embodiments of the present application, the swelling degree of the first organic matter in the electrolyte is 40% to 150%. For example, the swelling degree of the first organic matter in the electrolyte can be 40%, 50%, 58%, 60%, 70%, 77%, 80%, 89%, 90%, 100%, 120%, 140%, 150% or a range consisting of any two of the numerical values. By regulating the swelling degree of the first organic matter in the electrolyte within the above range, the storage capacity of the battery separator for the electrolyte can be improved, the bite area and bite force of the first organic matter and the inorganic particles and the porous substrate layer can be increased, and the shedding of inorganic particles during the charge and discharge process of the secondary battery can be reduced. At the same time, the probability of the first organic matter penetrating into the pores in the porous substrate layer is reduced, the transmission channel of lithium ions is increased, and the transmission internal resistance and lithium ion loss of lithium ions are reduced, thereby helping to improve the anti-breakdown voltage capability and peel strength of the battery separator and improve the performance of the secondary battery, such as cycle performance.

[0061] In some embodiments of the present application, the glass transition temperature of the first organic compound is between -40°C and 100°C, and the temperature range of the glass transition temperature is ≤12°C, wherein the temperature range of the glass transition temperature is the difference between the end point and the starting point of the glass transition temperature. For example, the glass transition temperature of the first organic compound can be -40°C, -20°C, 0°C, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, or a range consisting of any two values ​​therein, and the temperature range of the glass transition temperature can be 0°C, 2°C, 4°C, 6°C, 8°C, 10°C, 12°C, or a range consisting of any two values ​​therein. By regulating the glass transition temperature of the first organic matter and the temperature domain of the glass transition temperature within the above-mentioned range, it is beneficial to form a coating with uniform distribution of components during the coating slurry coating and drying process, increase the contact area between the first organic matter and the porous substrate layer, and improve the peel strength between the coating and the porous substrate layer. At the same time, the rigidity of the prepared battery separator can be reduced, and the probability of powder loss of the coating can be reduced in the subsequent preparation process of the secondary battery (such as slitting and winding), which is beneficial to improve the battery separator's anti-breakdown voltage capability and peel strength.

[0062] In some embodiments of the present application, the shear retention rate of the first organic matter is 0 to 0.08%. For example, the shear retention rate of the first organic matter can be 0, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08% or a range consisting of any two of these values. In the present application, the shear retention rate refers to placing a first organic matter of mass m1 in a 1000 rpm stirrer and stirring for 10 minutes, then filtering the first organic matter with a 200-mesh sieve, and the mass of the first organic matter remaining on the filter is m2, then the shear retention rate = m2 / m1×100%. Regulating the shear retention rate of the first organic matter within the above range is beneficial to improving the anti-breakdown voltage capability and peel strength of the battery separator.

[0063] In some embodiments, the organic matter includes a second organic matter, which is a leveling agent. The second organic matter can be a polysaccharide compound, which can be selected from at least one of a natural polymer compound or a cellulose semi-synthetic polymer compound. The use of this second organic matter can regulate the viscosity of the coating slurry, improve the dispersibility of the inorganic particles in the coating slurry, and ensure a uniform distribution of the components of the prepared coating, achieving a better coating effect and improving the heat resistance of the battery separator, thereby facilitating the improvement of the battery separator's breakdown voltage resistance and peel strength. To improve the dispersibility of the inorganic particles, the second organic matter can be a cellulose semi-synthetic polymer compound.

[0064] In some embodiments, the mass percentage of the second organic matter is W based on the mass of the coating. 22 , meeting: 0%≤W 22 ≤7%. For example, W 22 The value of can be 0%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 5%, 6%, 6.5%, 7% or a range consisting of any two of them. 22 The value of is within the above range, which can improve the heat resistance of the battery separator and make the components of the prepared coating evenly distributed, which is beneficial to improving the breakdown voltage resistance and peel strength of the battery separator.

[0065] In some embodiments, the degree of etherification of the cellulose semi-synthetic polymer compound is between 0 and 3, optionally between 0.5 and 1.2, further optionally between 0.5 and 1, and even further optionally between 0.7 and 1. For example, the degree of etherification of the cellulose semi-synthetic polymer compound can be 0, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.7, 2, 2.2, 2.5, 3, or a range consisting of any two of these values. By regulating the degree of etherification of the cellulose semi-synthetic polymer compound within the above range, the dispersibility of the inorganic particles in the coating slurry is improved, the water content in the battery separator is reduced, and the occurrence of side reactions is minimized, thereby improving the breakdown voltage and peel strength of the battery separator. In this application, the degree of etherification refers to the degree of substitution of the three hydroxyl groups of each anhydroglucose unit in the cellulose with substituents such as carboxymethyl groups.

[0066] In some embodiments, the average degree of polymerization of the cellulose semi-synthetic polymer compound is 1200 to 3000, optionally 1400 to 3000, further optionally 1400 to 2500, and particularly optionally 1400 to 1500. For example, the average degree of polymerization of the cellulose semi-synthetic polymer compound can be 1200, 1400, 1450, 1500, 1800, 2000, 2200, 2500, 2800, 3000, or a range consisting of any two of these values. By regulating the average degree of polymerization of the cellulose semi-synthetic polymer compound within the above range, it is beneficial to make the coating slurry have suitable fluidity, improve the stability and uniformity of the coating slurry, achieve a good coating effect, and make the components of the prepared coating uniformly distributed, thereby facilitating the improvement of the breakdown voltage resistance and peel strength of the battery separator.

[0067] In some embodiments, the cellulose semi-synthetic polymer compound may be selected from at least one of carboxymethyl cellulose, methyl cellulose, sodium carboxymethyl cellulose, hydroxyethyl cellulose, or sodium hydroxyethyl cellulose.

[0068] In some embodiments, the second organic compound may also be selected from at least one of styrene maleic anhydride, phenolic resin, or polyurethane.

[0069] The present application does not specifically limit the type of organic matter, as long as the ratio (1-C / H / A) × P / H calculated using the density and mass percentage of the organic matter in the coating falls within the scope of this application. For example, the organic matter may include at least one of a first organic matter, a second organic matter, a wetting agent, or a dispersant, and may also include other organic matter that can be used in the coating. In some embodiments, the organic matter in the coating may be the first organic matter; in other embodiments, the organic matter in the coating may be the first organic matter and the second organic matter.

[0070] In some embodiments, the coating includes inorganic particles, a first organic matter, and a second organic matter, and may further include a wetting agent and a dispersant. Based on the mass of the coating, the mass percentage of the wetting agent may be 0% to 1%, and the mass percentage of the dispersant may be 0% to 1%. The present application has no particular restrictions on the types of wetting agents and dispersants, as long as the purpose of the present application can be achieved. For example, the wetting agent may be selected from, but not limited to, at least one of polyether-modified polysiloxanes, polysiloxanes, methyl acrylate polymers, dodecylphenol polyoxyethylene ethers, polyoxyethylene carboxylates, polyoxyethylene alkyl ethers, or fatty alcohol polyvinyl ether sodium sulfate, and the dispersant may be selected from, but not limited to, at least one of polycarboxylates, ammonium polyacrylates, or polyvinyl alcohol.

[0071] In some embodiments, the thickness of the porous substrate layer is 0.3 μm to 30 μm, preferably 0.5 μm to 20 μm, and more preferably 3 μm to 15 μm. For example, the thickness of the porous substrate layer can be 0.3 μm, 0.5 μm, 1 μm, 3 μm, 5 μm, 5.2 μm, 6 μm, 7 μm, 7.1 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, or a range consisting of any two of these values. By regulating the thickness of the porous substrate layer within the above range, it is beneficial to the permeation and migration of ions in the electrolyte, which is beneficial to improving the breakdown voltage resistance and peel strength of the battery separator. At the same time, it is beneficial to improve the energy density of secondary batteries when applied to them.

[0072] In some embodiments, the porosity of the porous substrate layer is 10% to 70%, preferably 20% to 60%. For example, the porosity of the porous substrate layer can be 10%, 20%, 30%, 40%, 50%, 60%, 70%, or a range consisting of any two of these values. By regulating the porosity of the porous substrate layer within the above range, more transmission channels can be provided for ions, shortening the transmission distance of ions, and improving the ion transmission efficiency. At the same time, it is also beneficial to absorb and retain the electrolyte, enhance the wettability of the electrolyte to the battery separator, and help improve the anti-breakdown voltage capability and peel strength of the battery separator.

[0073] In some embodiments, the porous substrate layer is selected from a polyolefin substrate, a non-woven fabric substrate, or an electrospun substrate, preferably a polyolefin substrate. The use of the porous substrate layer is beneficial to improving the breakdown voltage resistance and peel strength of the battery separator.

[0074] In some embodiments, the polyolefin substrate is selected from any of single-layer polyethylene, single-layer polypropylene, multi-layer polyethylene, and multi-layer polypropylene. From the perspective of film-forming performance, the polyolefin substrate is preferably polyethylene and its copolymers, and may be at least one of ultra-high molecular weight polyethylene, high-density polyethylene, and low-density polyethylene. Polyethylene can be obtained through a one-step polymerization process or a multi-step polymerization process. The use of such polyolefin substrates further enhances the breakdown voltage resistance and peel strength of the battery separator.

[0075] In some embodiments, the molecular weight of the polyethylene is 300,000 to 5,000,000, preferably 400,000 to 4,000,000, more preferably 500,000 to 3,000,000. For example, the molecular weight of the polyethylene can be 300,000, 400,000, 500,000, 600,000, 800,000, 1,000,000, 1,500,000, 2,000,000, 2,400,000, 3,000,000, 3,500,000, 4,000,000, 4,500,000, 5,000,000, or a range consisting of any two of these values.

[0076] In other embodiments, the porous substrate layer may be a polyolefin substrate prepared by mixing a polyolefin with a molecular weight of 300,000 to 800,000 with a polyolefin with a molecular weight of 2,000,000 to 5,000,000. The use of such a polyolefin substrate further improves the battery separator's breakdown voltage resistance and peel strength. In this application, molecular weight refers to weight-average molecular weight.

[0077] In some embodiments, the polyethylene particle size is less than or equal to 500 μm. For example, the polyethylene particle size can be 250 μm, 300 μm, 400 μm, 500 μm, or a range consisting of any two of these values. In this application, the polyethylene particle size refers to the average particle size (Dv50) of the polyethylene masterbatch used to prepare the porous substrate layer.

[0078] In this application, the true density of inorganic particles can be tested using the gas volume method. Specifically, the inorganic particle sample is placed in a true density tester. The pressure is gradually increased to allow gas to enter the sample's pores. The pressure change is then recorded to determine the sample's volume and calculate the true density of the inorganic particles. The true density of inorganic particles can also be tested using the immersion method. Specifically, the inorganic particle powder to be tested is immersed in a liquid that wets but does not dissolve it. Vacuuming is performed to remove air bubbles. The volume of liquid displaced from a container of known capacity is then measured to calculate the true density of the inorganic particles. The bulk density of inorganic particles can be tested in accordance with GB / T 31057.1-2014, "Part 1: Determination of bulk density," and the density of organic materials can be tested in accordance with GB / T 611-2021, "General method for the determination of density of chemical reagents." The glass transition temperature of organic materials can be tested using differential scanning calorimetry (DSC).

[0079] The second aspect of the present application provides a method for preparing the battery separator provided in the first aspect of the present application, comprising the following steps: (1) providing a porous substrate layer; (2) providing a coating slurry comprising inorganic particles and organic matter, wherein the organic matter comprises a first organic matter; (3) coating the coating slurry on at least one (for example, one or two) surfaces of the porous substrate layer, and drying the coating slurry to obtain a battery separator comprising a coating.

[0080] The present application does not impose any particular restrictions on the production process of the porous substrate layer, as long as the purpose of the present application can be achieved. For example, the porous substrate layer can be produced by dry uniaxial stretching, biaxial synchronous or asynchronous stretching, or wet biaxial synchronous or asynchronous stretching, preferably by wet biaxial synchronous or asynchronous stretching.

[0081] The present application does not impose any particular restrictions on the production process of the inorganic particles, as long as the objectives of the present application can be achieved. For example, during the preparation of the inorganic particles, the steam inlet temperature can be 280°C to 300°C, the steam outlet temperature can be 115°C to 125°C, and the steaming time can be 5 minutes to 20 minutes.

[0082] In some embodiments of the present application, the coating slurry includes 30-50 parts of inorganic particles, 2-30 parts of organic matter, and 40-70 parts of solvent.

[0083] In some embodiments of the present application, the organic matter includes at least one of a first organic matter, a second organic matter, a dispersant, or a wetting agent.

[0084] In some embodiments of the present application, the coating slurry includes 30-50 parts of inorganic particles, 2-10 parts of the first organic matter, and 40-70 parts of solvent. In other embodiments, the coating slurry includes 30-50 parts of inorganic particles, 2-10 parts of the first organic matter, 0.5-10 parts of the second organic matter, and 40-70 parts of solvent.

[0085] In yet other embodiments, the coating slurry includes inorganic particles, a first organic material, a second organic material, a dispersant, a wetting agent, and a solvent.

[0086] This application does not specifically limit the type of solvent, as long as it can achieve the objectives of this application. For example, the solvent can be selected from, but is not limited to, pure water, N-methyl-2-pyrrolidone (NMP), or dimethylacetamide (DMAc). This application does not specifically limit the type of wetting agent and dispersant, as long as it can achieve the objectives of this application. For example, the wetting agent can be selected from, but is not limited to, at least one of polyether-modified polysiloxanes, polysiloxanes, methyl acrylate polymers, dodecylphenol polyoxyethylene ethers, polyoxyethylene carboxylates, polyoxyethylene alkyl ethers, or sodium fatty alcohol polyvinyl ether sulfates. The dispersant can be selected from, but is not limited to, at least one of polycarboxylates, ammonium polyacrylates, or polyvinyl alcohol. In this application, "parts" refers to parts by mass.

[0087] In some embodiments of the present application, when the first organic matter is added to the coating slurry, the flow rate of the first organic matter is 3L / min to 9L / min, and the temperature of the coating slurry is 18°C ​​to 30°C. For example, the flow rate of the first organic matter can be 3L / min, 4L / min, 5L / min, 6L / min, 7L / min, 8L / min, 9L / min, or a range consisting of any two values ​​therein, and the temperature of the coating slurry can be 18°C, 19°C, 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C, 30°C, or a range consisting of any two values ​​therein. By regulating the flow rate of the first organic matter and the temperature of the coating slurry within the above range, the charge instability of the coating slurry caused by the instantaneous addition of the first organic matter can be effectively avoided, the micelle-like black spots generated in the coating after coating due to the instantaneous film formation of the first organic matter can be reduced, and the problem of uneven distribution of the first organic matter particles in the coating can be improved, which is beneficial to improving the anti-breakdown voltage capability and peel strength of the battery separator.

[0088] In some embodiments of the present application, the pH of the coating slurry is 7 to 10, preferably 7.5 to 9.5; the viscosity of the coating slurry is 5 mPa·s to 200 mPa·s, preferably 10 mPa·s to 80 mPa·s, more preferably 20 mPa·s to 60 mPa·s; the PSD of the particles in the coating slurry is 0.25 μm to 0.5 μm. For example, the pH of the coating slurry can be 7, 7.5, 8, 8.5, 9, 9.5, 10, or a range consisting of any two values ​​therein; the viscosity of the coating slurry can be 5 mPa·s, 20 mPa·s, 40 mPa·s, 60 mPa·s, 80 mPa·s, 100 mPa·s, 120 mPa·s, 140 mPa·s, 160 mPa·s, 180 mPa·s, 200 mPa·s, or a range consisting of any two values ​​therein; the PSD of the particles in the coating slurry can be 0.25 μm, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm, 0.5 μm, or a range consisting of any two values ​​therein. The suspension stability of the coating slurry is above 95%, which refers to the ratio of the suspension height to the initial liquid level after the coating slurry is prepared and allowed to stand for 2 hours. By regulating the coating slurry to meet the above conditions, it is beneficial to improve the stability and uniformity of the coating slurry, so that the components of the prepared coating are evenly distributed, ensuring that the surface flatness of the coated coating is high, which is beneficial to improving the battery separator's anti-breakdown voltage capability and peel strength.

[0089] In some embodiments of the present application, during the coating process of the coating slurry, the ratio of the adsorption roller frequency to the thickness of the porous substrate layer is 4.8 Hz / μm to 6 Hz / μm. For example, the ratio of the adsorption roller frequency to the thickness of the porous substrate layer can be 4.8 Hz / μm, 5.0 Hz / μm, 5.2 Hz / μm, 5.4 Hz / μm, 5.6 Hz / μm, 5.8 Hz / μm, 6 Hz / μm, or a range consisting of any two of these values. By regulating the ratio of the adsorption roller frequency to the thickness of the porous substrate layer within the above range, it can be ensured that the surface flatness of the applied coating is high and there is no foreign matter on the surface, which is beneficial to improving the anti-breakdown voltage capability and peel strength of the battery separator.

[0090] In some embodiments of the present application, the absolute difference between the drying oven temperature and the glass transition temperature of the first organic compound is 20°C to 65°C. For example, the absolute difference between the drying oven temperature and the glass transition temperature of the first organic compound can be 20°C, 30°C, 40°C, 50°C, 60°C, 65°C, or a range consisting of any two of these values. By regulating the absolute difference between the drying oven temperature and the glass transition temperature of the first organic compound to be within the above range, the battery separator's breakdown voltage capability and peel strength can be improved.

[0091] In this application, the porous substrate layer, inorganic particles, first organic compound, second organic compound, dispersant, wetting agent, etc. are all commercially available conventional substances. This application does not specifically limit their sources, as long as they can achieve the purpose of this application. This application can be tested in conjunction with corresponding test methods to select the desired porous substrate layer, inorganic particles, first organic compound, second organic compound, dispersant, wetting agent, etc.

[0092] The third aspect of the present application provides a secondary battery comprising the battery separator provided in the first aspect of the present application or the battery separator prepared by the preparation method provided in the second aspect. The battery separator provided in the present application has good breakdown voltage resistance and high peel strength, thereby providing the secondary battery provided in the present application with good performance, such as safety performance.

[0093] The secondary battery of the present application also includes a positive electrode sheet, a negative electrode sheet, and an electrolyte. The present application has no particular restrictions on the positive electrode sheet, the negative electrode sheet, and the electrolyte, and those skilled in the art can select them according to actual needs as long as they can achieve the purpose of the present application.

[0094] The present application does not particularly limit the type of secondary battery, which may include any device that undergoes an electrochemical reaction. For example, secondary batteries may include, but are not limited to, lithium-ion secondary batteries (Li-ion batteries), lithium metal secondary batteries, sodium-ion secondary batteries (Na-ion batteries), lithium polymer secondary batteries, and lithium-ion polymer secondary batteries.

[0095] Example Hereinafter, the embodiments of the present application will be described in more detail with reference to Examples and Comparative Examples. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are by mass.

[0096] Test methods and equipment: Coating surface density test Using a 10 cm x 10 cm mold, five square specimens of each of the porous substrate layer and the coated battery separator were cut in the transverse direction (TD) for testing. If the TD dimension is less than 10 cm, a 10 cm specimen was cut in the machine direction (MD). In this case, the specimen is not square. The specimens were weighed using an analytical balance with a measurement accuracy of 0.0001 g. The areal density of the porous substrate layer = mass of the porous substrate layer specimen / (porous substrate layer specimen length × porous substrate layer specimen width), the coating areal density of the battery separator = mass of the battery separator specimen / (battery separator specimen length × battery separator specimen width), and the coating areal density = battery separator coating areal density - porous substrate layer areal density. The average of the five specimens was used as the areal density of the porous substrate layer, the coating areal density of the battery separator, and the coating areal density of the coating. The longitudinal direction refers to the length of the battery separator, and the transverse direction refers to the width of the battery separator.

[0097] Thickness test The test was carried out with reference to the requirements of GB / T6672-2001 "Plastic film and sheeting - Mechanical measurement method for thickness".

[0098] Using a 10 cm x 10 cm mold, five square specimens of each of the porous substrate layer and the coated battery separator were cut along the TD direction for testing. If the TD dimension is less than 10 cm, a 10 cm specimen was cut along the MD direction; in this case, the specimen is not square. A Mahr C1202 thickness gauge was used to measure the four corners and the center of the specimen. The average of these five measurements was used as the thickness of the individual specimen. The average of these five measurements was used as the thickness of the porous substrate layer and the battery separator. The coating thickness = battery separator thickness - porous substrate thickness.

[0099] Air permeability test The test was conducted in accordance with JIS P 8117-2009, "Paper and paperboard. Determination of air permeability and air resistance (medium range). Gurley method." 600mm x 100mm porous substrate layer and coated battery separator specimens were cut and tested using a Wangyan air permeometer (Asahi Co., Ltd., EG01-55-1MR) for 3 seconds. The air permeability of the porous substrate layer and battery separator was measured at random locations every 100mm along the 600mm TD direction. The average of these five test points was recorded as the air permeability of the porous substrate layer and battery separator. The added air permeability of the battery separator is calculated as: air permeability of the battery separator minus air permeability of the porous substrate layer.

[0100] Particle size testing Using a laser particle size analyzer (Dandong Better, BT-2600E), we measured the Dv10, Dv25, Dv50, Dv75, and Dv90 values ​​of the inorganic particles, and calculated the PSD. Specific particle size measurements were conducted in accordance with the national standard GB / T19077-2016, "Particle Size Distribution by Laser Diffraction Method."

[0101] Test of the mass ratio of hydroxyl groups on the surface of inorganic particles (1) Preparation of NaCl solution: Weigh 400 g of NaCl into a 2 L beaker, add 1.75 L of water to dissolve, adjust the pH to 3.0 ± 0.1 with hydrochloric acid, and take 150 ml of the above NaCl solution; (2) Preparation of sodium hydroxide standard solution: c(NaOH) = 0.1 mol / L, according to GB / T 601-2016 Chapter 4 4.1 Preparation and calibration of sodium hydroxide standard titration solution; (3) Blank sample addition: titrate with NaOH standard solution at a rate of 20 seconds / drop. When the pH value of the solution reaches 4.0±0.1, the scale value at this time is recorded as V1; continue titrating until the pH reaches 9.0±0.1. After the pH value of the solution reaches 8.0, reduce the titration speed to 20 seconds / half drop. When the pH value changes less than 0.02 within 10 seconds, record the burette scale V2 and calculate the volume of sodium hydroxide solution consumed during the period from pH 4.0 to 9.0 (V) 空白 =V2-V1; (4) Preparation of sample solution: Weigh the inorganic particle sample m after drying at 105℃ for 2h using an analytical balance. 样品 Place 1.5 g (accurate to 1 mg) in a 250 ml beaker, add 150 ml of sodium chloride solution, place a stirring bar in a magnetic stirrer and stir evenly, then keep the temperature at 25 ± 0.5 ° C and titrate; (5) Sample titration: titrate the inorganic particle sample solution at a rate of 3-4 drops per second. When the pH value reaches the end point, slow down the titration speed and record and calculate the volume of sodium hydroxide standard solution V consumed when the solution pH changes from 4.0 to 9.0. NaOH ; (6) Calculation of surface hydroxyl mass ratio: w(OH)= (V NaOH -V 空白 )×c(NaOH)×17.007 / (m 样品 ×1000), where V NaOH 、V 空白 The unit of is mL, the unit of c(NaOH) is mol / L, m 样品 The unit is g.

[0102] Electrolyte swelling test The first organic matter sample is placed at 105°C for drying. When the sample is dried to a constant weight (the deviation between two weighings is within 0.2g), the dried sample is weighed and the mass is recorded as M1. Then, the sample is placed in an electrolyte with a mass ratio of dimethyl carbonate DMC, ethyl methyl carbonate EMC, and diethyl carbonate DEC of 1:1:1 and placed at 25°C for 24 hours. The sample is taken out, the residual electrolyte on the surface is wiped off, and the mass of the sample after soaking in the electrolyte is weighed and the mass is recorded as M2. The swelling degree of the first organic matter = (M2-M1) / M1.

[0103] Shear retention test A first organic matter with a mass of m1 is placed in a 1000 rpm stirrer and stirred for 10 minutes, and then the first organic matter is filtered through a 200-mesh sieve. The mass of the first organic matter remaining on the filter is m2. The shear retention rate = m2 / m1×100%.

[0104] Peel strength test Use a 2.5cm×30cm mold to cut a coated battery separator sample. Paste the double-sided adhesive tape used for peel strength testing onto the test plate. Tear off the surface sticker of the double-sided adhesive tape, leaving only the sticker of about 2cm at the end. Attach the battery separator sample flatly to the end of the double-sided adhesive tape where the sticker is torn off, with the coated side in contact with the double-sided adhesive tape. Roll back and forth three times with a pressure roller, then manually peel 1cm off the coating and the porous substrate layer to make a sample strip to be tested. Clamp the end of the sample strip with the residual sticker between the lower chuck of a tensile testing machine (Jinan Sike Testing Technology Co., Ltd., TSL-1002), and clamp the other end of the sample strip to the upper chuck to ensure that the sample strip is not tilted. The tensile speed of the tensile testing machine is 50mm / min. Measure the load when the coating is peeled off from the porous substrate layer. The average of the three measurements is taken as the peel strength between the coating and the porous substrate layer.

[0105] Breakdown voltage test A 600mm×100mm coated battery separator was cut and an insulation tester (KIKUSUI, TOS9301) was used with a buffer time of 10s, a test time of 10s, and a cut-off voltage of 6kV. Tests were performed at random locations every 100mm along the 600mmTD direction. The test data were recorded and the average value of the test data at the five points was recorded as the breakdown voltage of the battery separator.

[0106] Example 1 <Preparation of coating slurry> Carboxymethyl cellulose (density 1.02 g / cm 3 ) was dissolved in water to prepare a second organic solution with a mass concentration of 5% for standby use.

[0107] 60 parts by weight of solvent water was added to a double planetary mixer, and 35 parts by weight of inorganic boehmite particles were added and stirred uniformly. Then, 5.6 parts by weight of a second organic solution was added and stirred uniformly. Finally, 4 parts by weight of a first organic acrylic resin emulsion was added and stirred uniformly to obtain a coating slurry. The slurry temperature was 23.4°C when the first organic solution was added, and the first organic solution was added at a rate of 6.5 L / min. The resulting coating slurry had a solids content of 35%, a pH of 8.38, a viscosity of 28.2 mPa·s, and a PSD of 0.46 μm.

[0108] The bulk density D3 of the inorganic particles in this embodiment is 0.42 g / cm 3 , true density D1 is 3.04g / cm 3 , PSD is 0.61μm, Dv50 is 0.84μm, the surface hydroxyl mass ratio is 0.04%, and the parameter conditions in the preparation process are: steam foam inlet temperature is 285.4℃, steam outlet temperature is 116℃, and steam foam time is 6min.

[0109] In this embodiment, the first organic matter is acrylic resin (density 1.15g / cm 3 ), its swelling degree in the electrolyte is 77%, the glass transition temperature is -36.7℃, the temperature range of the glass transition temperature is 5.3℃, and the shear retention rate is 0.02%.

[0110] <Preparation of Battery Separator> A polyethylene film is used as the porous substrate layer, wherein the thickness of the porous substrate layer is 7.1 μm and the surface density is 4.36 g / m 2 , air permeability is 142 s / 100cc.

[0111] The coating slurry was applied to one surface of the porous substrate layer. During the coating process, the ratio of the adsorption roller frequency to the thickness of the porous substrate layer was 5.63 Hz / μm. The porous substrate layer coated with the coating slurry was dried in an oven. The absolute difference between the oven temperature during the drying process and the glass transition temperature of the first organic compound was 23.3°C to obtain a battery separator. The coating thickness of the battery separator was 2.1 μm and the surface density was 7.47 g / m 2 , coating surface density is 3.11g / m 2 , air permeability is 154 s / 100cc, and air permeability increase is 12 s / 100cc.

[0112] Example 2 In addition to adjusting the relevant parameters according to Table 1 and coating the porous substrate layer on both sides, the single-side coating thickness is 1.1 μm and the single-side coating surface density is 1.605 g / m 2 Other than that, the rest is the same as Example 1.

[0113] Example 3 to Example 4 Except for adjusting the relevant parameters according to Table 1, the rest is the same as Example 1.

[0114] Example 5 In addition to adjusting the relevant parameters according to Table 1 and coating the porous substrate layer on both sides, the single-side coating thickness is 1 μm and the single-side coating surface density is 1.455 g / m 2 Other than that, the rest is the same as Example 1.

[0115] Comparative Examples 1 to 5 Except for adjusting the relevant parameters according to Table 1, the rest is the same as Example 1.

[0116] The preparation parameters and performance parameters of each embodiment and comparative example are shown in Table 1.

[0117] Table 1

[0118] Note: The “amount used” in Table 1 refers to the mass fraction of each substance (including the solvent of each substance) in the coating slurry, the “solid amount fraction” refers to the mass fraction of each substance (excluding the solvent of each substance) in the coating slurry, the “coating proportion” refers to the mass proportion of each substance (excluding the solvent of each substance) in the prepared coating, and the “slurry proportion” refers to the mass proportion of each substance (including the solvent of each substance) in the coating slurry.

[0119] As can be seen from Examples 1 to 5 and Comparative Examples 1 to 5, by adjusting the value of (1-C / H / A) × P / H for the battery separator within the range of this application, the battery separator has a high breakdown voltage and high peel strength, and has good breakdown voltage resistance. However, the battery separators of Comparative Examples 1 to 5 have values ​​of (1-C / H / A) × P / H outside the range of this application, and the breakdown voltage and peel strength of the battery separator are relatively low, indicating that the battery separator has poor breakdown voltage resistance.

[0120] It should be noted that, in this document, relational terms such as first and second, etc., are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the terms "comprises," "comprising," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a list of elements includes not only those elements but also other elements not explicitly listed, or elements inherent to such process, method, article, or apparatus.

[0121] Each embodiment in this specification is described in a related manner. The same or similar parts between the embodiments can be referred to each other. Each embodiment focuses on the differences from other embodiments.

[0122] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. A battery separator, comprising a porous substrate layer and a coating disposed on at least one surface of the porous substrate layer, wherein the coating comprises inorganic particles and organic matter, The coating surface density of the coating is C g / m 2 , the thickness of the coating is H μm, the air permeability increase of the battery separator is P s / 100cc, and the true density of the inorganic particles is D1 g / cm 3 , the density of the organic matter is D 2i g / cm 3 Based on the mass of the coating, the mass percentage of the inorganic particles is W1, and the mass percentage of the organic matter is W 2i , satisfying: 2≤(1-C / H / A)×P / H≤10, where, , n is the number of types of the organic matter; The peel strength between the coating layer and the porous substrate layer is ≥20 gf / 15 mm, and the breakdown voltage of the battery separator is ≥0.5 kV.

2. The battery separator according to claim 1, wherein The mass percentage of the inorganic particles meets the following requirements: 82%≤W1≤97%, and the mass percentage of the organic matter meets the following requirements: 3%≤ ≤18%.

3. The battery separator according to claim 1, wherein The thickness of the coating satisfies: 0.5≤H≤8, and the coating surface density of the coating satisfies: 1≤C≤10.

4. The battery separator according to claim 1, wherein The bulk density of the inorganic particles is D3 g / cm 3 , the inorganic particles satisfy: 2.3≤D1-D3≤3.

1.

5. The battery separator according to claim 1, wherein The particle size PSD of the inorganic particles satisfies: 0.38 μm ≤ PSD ≤ 0.63 μm, wherein, 。 6. The battery separator according to claim 1, wherein The surface hydroxyl groups of the inorganic particles account for 0 to 0.06% by mass.

7. The battery separator according to claim 1, wherein The inorganic particles are selected from at least one of silicon dioxide, aluminum oxide, magnesium oxide, zirconium oxide, titanium oxide, calcium oxide, boehmite, aluminum nitride, boron nitride, barium sulfate, calcium fluoride, barium fluoride or barium titanate.

8. The battery separator according to claim 1, wherein The organic matter comprises a first organic matter, and the first organic matter is selected from at least one of styrene-butadiene rubber, acrylic resin, polyvinyl alcohol, polyacrylonitrile, polyvinylidene fluoride, polyethylene oxide, polytetrafluoroethylene, acrylic acid and its derivative copolymers or acrylamide and its derivative copolymers, Based on the mass of the coating, the mass percentage of the first organic matter is W 21 , which satisfies: 3%≤W 21 ≤10%.

9. The battery separator according to claim 8, wherein: The first organic matter satisfies at least one of the following characteristics: (1) The swelling degree of the first organic matter in the electrolyte is 40% to 150%; (2) The glass transition temperature of the first organic substance is between -40°C and 100°C, and the temperature range of the glass transition temperature is ≤12°C, wherein the temperature range of the glass transition temperature is the difference between the end point and the start point of the glass transition temperature; (3) The shear retention rate of the first organic matter is 0 to 0.08%.

10. A method for preparing a battery separator according to any one of claims 1 to 9, comprising the following steps: (1) providing a porous substrate layer; (2) providing a coating slurry including inorganic particles and organic matter, wherein the organic matter includes a first organic matter; (3) The coating slurry is coated on at least one surface of the porous substrate layer, and dried to obtain a battery separator including the coating layer.

11. The preparation method according to claim 10, which satisfies at least one of the following characteristics: (1) The coating slurry comprises 30-50 parts of inorganic particles, 2-10 parts of a first organic matter and 40-70 parts of a solvent; (2) When the first organic matter is added to the coating slurry, the flow rate of the first organic matter is 3 L / min to 9 L / min, and the temperature of the coating slurry is 18° C. to 30° C.; (3) The pH of the coating slurry is 7 to 10, the viscosity is 5 mPa·s to 200 mPa·s, and the PSD of the particles in the coating slurry is 0.25 μm to 0.5 μm; (4) during the coating process of the coating slurry, the ratio of the adsorption roller frequency to the thickness of the porous substrate layer is 4.8 Hz / μm to 6 Hz / μm; (5) The absolute value difference between the oven temperature of the drying process and the glass transition temperature of the first organic matter is 20° C. to 65° C. 12 . A secondary battery comprising the battery separator according to claim 1 or the battery separator prepared by the preparation method according to claim 10 or 11.

Citation Information

Patent Citations

  • Separator for electrochemical device and electrochemical device comprising same

    CN117730454A

  • Lithium battery diaphragm, coating slurry, and preparation method and application of coating slurry

    CN118867581A